Present, past and human relationships in Penelope Lively's novels - Štykarová, Martina (2006)
The thesis explores the continuity of time and the parallels between the past and present in Penelope Lively's novels. It focuses on the personal and family history and its influence on human relationships. The selected novels include Moon Tiger, Passing On and Heat Wave